In situ measurement of spectral linewidth in wavelength-modulated signals for frequency-modulated continuous-wave LiDAR systems - Jongpil La; Munhyun Han; Jieun Choi; Bongki Mheen (AIP Advances, 2024)
This paper advances an in situ method to measure the spectral linewidth directly from the currently generated wavelength-modulated signals in frequency-modulated continuous-wave (FMCW) light detection and ranging (LiDAR) systems, diverging from traditional methods that focus on the linewidth of the original unmodulated laser source. Our approach, employing a self-heterodyne technique with a short-delay line, specifically targets the modulated signal’s linewidth in real-time, which is vital for the operational fidelity of FMCW LiDAR systems. Crucially, our method leverages the unique capabilities of an optical hybrid for accurate phase noise and linewidth measurements, distinguishing it from conventional beat frequency extraction techniques. For the evaluation of the spectral linewidth measurement, a frequency-modulated laser source based on an optical phase-locked loop configuration was first described where the laser achieves linear optical frequency modulation by controlling the injection current of an external cavity diode laser (ECDL). The phase error measured from a Mach–Zehnder interferometer signal is used to detect the frequency deviation error from the target value, which is then fed back to the driving current of the ECDL to compensate it. Utilizing the proposed method, the laser’s linewidth for the fabricated FMCW LiDAR was measured to be 287 kHz, exhibiting a clear Lorentzian spectrum shape, where the spectral modulation bandwidth and sweep time were 2.91 GHz and 50 µs, respectively. The results clearly demonstrate that the proposed in situ spectral linewidth measurement provides an efficient method for performance monitoring of FMCW LiDAR.